2008
DOI: 10.1002/cjce.20110
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the issues of equilibrium in the Fischer–Tropsch synthesis

Abstract: The product distribution for the Fischer-Tropsch synthesis is normally described using the kinetically derived (Anderson-Schultz-Flory) ASF model. Variations of the kinetic model have been proposed to explain deviations from the ASF distribution. The Fischer-Tropsch system can be equally well described using a pseudo-element (CH 2 , H 2 , O) equilibrium approach. A one-parameter equilibrium model is derived for the product distributions for alkenes, alkanes and alcohols.The Fischer-Tropsch system should be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…Their formation is dependent on process conditions e.g. n-alcohol formation becomes more favourable with increasing pressure (van der Laan, 1999;Norval, 2008). This is shown by the 30-40 bar(a) pressure conditions of the Qian et al (2013) experiments.…”
Section: Literature Reviewmentioning
confidence: 93%
See 3 more Smart Citations
“…Their formation is dependent on process conditions e.g. n-alcohol formation becomes more favourable with increasing pressure (van der Laan, 1999;Norval, 2008). This is shown by the 30-40 bar(a) pressure conditions of the Qian et al (2013) experiments.…”
Section: Literature Reviewmentioning
confidence: 93%
“…The work of Norval & Phillips (1990) and Norval (2008) has shown that the products of FT synthesis are distributed according to thermodynamics, with the yield of hydrocarbons controlled kinetically. This arises because the rates of chain growth are much faster than the rate of monomer formation from CO (Norval, 2008;Allie & Nyathi, 2019;Hensen et al, 2020). If FT synthesis could be modelled as equilibrium-controlled process, the kinetic model could consist of simpler rate…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the Flory distribution is usually derived from kinetics, modifications to this model, such as chain-length dependent termination probabilities, have been necessary to explain experimental results. Based on previous publications and some examples, Norval (132) argued that a one-parameter equilibrium model based on a pseudo-element (CH 2 , H 2 , CO) approach could be used to describe the product distribution for olefins, paraffins and alcohols. In Fig.…”
Section: Theoretical Workmentioning
confidence: 99%